Specificity of nucleoside transport in Neurospora crassa. - Dunaway-Mariano, D (1978)
The specificity of nucleoside uptake in germinating conidia of Neurospora crassa was investigated by examining the kinetics of [2-14C]uridine and [8-14C]-adenosine uptake in the wild-type, ad-8, and ud-1 pyr-1 strains. The results obtained strongly indicate that nucleoside transport in N. crassa is mediated solely by a general transport system which accepts both purine and pyrimidine nucleosides. Studies directed at characterizing the specificity of the transport system indicate that general structural features of the nucleoside which enhance its efficiency in binding to the transport system include: (i) a purine or pyrimidine as the heterocyclic ring, (ii) an unfunctionalized ribose or 2'-deoxyribose as the sugar unit, (iii) a beta-configuration about the anomeric carbon, (iv) the absence of substituents at C8 in the purine series and at C5 and C6 in the pyrimidine series, (v) the presence of a C5-C6 double bond in the pyrimidine series, and (vi) the absence of a charge on the heterocyclic ring.